Debating Food Security Policy in Two Different Ideational Settings: A Comparison of Australia and Norway. (20th February 2017) - Farsund, Arild Aurvåg; Daugbjerg, Carsten
Abstract : Food security has emerged as a relatively new policy issue in agricultural policy making in developed countries. This policy problem is addressed within an institutional landscape in which agricultural ideas and institutions are well‐established. In this article, food security policy making in Australia and Norway is compared. In Australia, agricultural normalism (agricultural markets and production are considered to be similar to those of other economic sectors) has been dominant since the mid‐1980s, while Norwegian agricultural policy making has been dominated by agricultural exceptionalism (agriculture is considered a unique economic sector with special market and production conditions). It is demonstrated in the article how these two opposing institutionalised ideational foundations have influenced the nature of the food security debate in the two countries. In Australia, the debate emphasises the positive role of the market and trade in providing global food security. In Norway, the debate highlights the need to regulate market forces and restrict trade in order to allow countries to develop their own agricultural sectors.